Synthesis and Anti‐Oomycete Activity of Sulfonate Derivatives of Fenjuntong. Issue 4 (21st March 2022) - Che, Zhiping; Li, Yuanhao; Guo, Xiaolong; He, Jiaxuan; Zhang, Song; Zhu, Lina; Liu, Yibo; Wei, Ruxue; Yang, Yingjun; Huang, Xiaobo; Liu, Shengming; Chen, Genqiang; et al.
Abstract: In order to discover highly active fungicides, sixteen novel sulfonate derivatives of Fenjuntong were synthesized by structural modification of 2′‐hydroxybutyrophenone, and their anti‐oomycete activity against Phytophthora capsici Leonian was determined in this study. Among all tested compounds, compound 3b displayed more significant anti‐oomycete activity than the precursor Fenjuntong against P. capsici, and the EC50 values of 3b and Fenjuntong were 84.50 and 517.25 mg/L, respectively. By comparing the anti‐oomycete activity of compounds 3a –p, I‐a –p, and II‐a –p, the following conclusions were drawn: (1) Hydroxy group is well tolerated, and sulfonylation of hydroxy group enhances its anti‐oomycete activity. (2) The proper length of the ketone carbonyl chain is very important for their anti‐oomycete activity. (3) The presence of a site methoxy group in the structural skeleton is closely related to the anti‐oomycete activity. These important results will pave the way for further modification of Fenjuntong to develop potential new fungicides. Abstract :